Survival Outcomes and Treatment Decision by Human Papillomavirus Status Among Patients With Stage IVC Head and Neck Squamous Cell Carcinoma - Zhou, Ping; Yu, Yi-Feng; Lian, Chen-Lu; Wang, Jun; Zhuo, Ren-Gong; Wu, San-Gang (Frontiers in Oncology, 2021)
Purpose: To investigate the influence of human papillomavirus (HPV) status on survival outcomes and treatment decisions for patients with de novo stage IV head and neck squamous cell cancers (HNSCC). Methods: Patients initially diagnosed with de novo stage IVC HNSCC between 2010 and 2015 were identified from the Surveillance, Epidemiology, and End Results database. Cox multivariable analyses were performed to determine prognostic factors associated with head and neck cancers specific survival (HNCSS) and overall survival (OS). Results: We identified 303 patients who received chemotherapy in this study, including 52.5% of them had HPV-positive disease. HPV-positive HNSCC had better HNCSS (P<0.001) and OS (P<0.001) compared to those with HPV-negative disease. The results of Cox multivariable analyses showed that HPV-negative status (P=0.007), N3 stage (P=0.004), bone metastases (P<0.001), and lung metastases (P=0.003) were associated with worse HNCSS. Similar results were found regarding the OS. The sensitivity analyses indicated that HPV-positive HNSCC patients who were treated with radiotherapy had better survival outcomes. However, no survival benefits were found in those with HPV-positive disease receiving surgery. For HPV-negative patients, no survival benefit was observed among those treated with radiotherapy or surgery. Conclusions: Approximately half of the stage IVC HNSCC patients are HPV-related. The presence of HPV infection appears to be strongly associated with the survival outcome in patients with de novo stage IV HNSCC. Determination of HPV status may help guide clinicians in prognostic assessment and treatment decision-making in this population.